Accumulation of 99mTc-DTPA in Lumbar Tuberculosis. (28th May 2022) - Yin, Hongyan; Yu, Haojun; Shi, Dai; Lv, Jing; Shi, Hongcheng
Abstract: A 70-year-old woman with lumbar and renal tuberculosis underwent 99m Tc-DTPA renal scintigraphy to evaluate renal function before lumbar lesion resection and nephrectomy. The images incidentally identified a focus of abnormal DTPA activity in the midline of the abdomen, which corresponded to lumbar tuberculosis revealed by CT images. Subsequent pathology after the resection of the lesions was consistent with lumbar and renal tuberculosis.